Accumulation of heavy metals and antioxidative enzymes of Centella asiatica in relation to metals of the soils. - Ong, G. H.; Yap, Chee Kong; Mahmood, Maziah; Tan, Soon Guan (Universiti Putra Malaysia, 2013)
Antioxidative enzymes have been claimed as being beneficial for enhancing fitness and for preventing disorders in plants due to the production of reactive oxygen species (ROS) caused by heavy metal stresses. Centella asiatica plants and soil sediments from nine sampling sites were collected between May and June of 2010. They were tested for their Cd, Cu, Fe, Ni, Pb and Zn contents. The plants were also analyzed for the activities of antioxidative enzymes namely superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and guaiacol peroxidase (GPX). This study revealed positive and significant (P<0.05) correlations between plants (leaves and roots) and soils for Cd, Zn, Ni and Fe content. It also showed that the significant correlations between Cd, Fe and Pb accumulations did not seem to be a factor for the increase in antioxidative enzyme activities due to their low concentrations in the plant; but the accumulated Cu, Zn and Ni levels were significantly (P<0.05) correlated with increases in antioxidative activities.